Additions to the description of Yunnaniata konstantinovi Lopatin, 2009, and its classification in the section Capulites (Coleoptera: Chrysomelidae: Galerucinae: Hylaspini) - Bezděk, Jan; Beenen, Ron (Zootaxa, 2009)
The taxonomic position of the genus Yunnaniata Lopatin, 2009 is discussed based on material from Yunnan. In our opinion, the genus Yunnaniata should be classified in the section Capulites Ogloblin, 1936, and is very close to the genus Capula Jacobson, 1925. The description of Yunnaniata konstantinovi Lopatin, 2009 is extended including the description of the sexual dimorphism. The spermatheca is illustrated. A list of species classified in Capulites and an identification key to genera of Capulites are given.